RESOLVING FINANCING PROBLEMS WITH RESTRUCTURING OF MURABAHAH FINANCING DURING THE COVID-19 PANDEMIC AT PT. SUMUT BANK (SHARIAH BUSINESS UNIT) - Fadillah, Muhammad Aris; Anggraini, Tuti; Inayah, Nurul (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research aims to analyze howresolving problematic financing by restructuring murabahah financing during the Covid-19 pandemic at PT. Bank Sumut (Sharia Business Unit).This research uses a qualitative type of research with a case study approach using data collection techniques through observation and interviews with related parties from Bank Sumut. The results of the research show that the practice of restructuring murabahah financing at Bank Sumut is carried out as an effort to rescue problematic financing. When viewed from POJK, especially POJK 48, the implementation of restructuring shows several important points that banks must pay attention to. Bank Sumut has guidelines for determining debtors affected by COVID-19. Apart from that, the restructuring implementation takes into account the MUI DSN Fatwa No. 47,48,49, regarding the resolution of problematic murabahah financing, the absence of additional costs and contract conversion Keywords: Problematic Financing, Restructuring, Murabahah Financing, Covid 19